PLK1 Mitigates Intervertebral Disc Degeneration by Delaying Senescence of Nucleus Pulposus Cells - Zhang, Zhenlei; Huang, Yizhen; Xu, Nizhen; Wang, Jianle; Yao, Teng; Xu, Yining; Qiao, Di; Gao, Jun; Shen, Shuying; Ma, Jianjun (Frontiers in Cell and Developmental Biology, 2022)
Intervertebral disc degeneration (IVDD) is the primary cause of low back pain; however, the molecular mechanisms involved in the pathogenesis of IVDD are not fully understood. Polo-like kinase 1 (PLK1) plays numerous roles in the cell cycle, including in cell proliferation and senescence. To investigate the involvement of PLK1 in IVDD, we used patient tissues and an animal model of IVDD. Samples were analyzed via immunoblotting, quantitative real-time polymerase chain reaction (qPCR), immunofluorescence, and immunohistochemistry. Our results demonstrated that PLK1 expression was decreased in nucleus pulposus cells (NPCs) of degenerative IVDs. The inhibition of PLK1 kinase activity in normal NPCs increased the expression of p53 protein, inhibited cell proliferation, and induced senescence. Our results suggest that PLK1 regulates the degeneration of the IVD through p53, revealing the function and mechanism of PLK1 in IVDD and providing a theoretical basis and experimental evidence for the potential treatment of low back pain.